An evaluation of engineering periodical collections in Metro Manila - Manalo, Elenita R.; Salazar, Elizabeth L. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1998)
The objectives of this study are to evaluate the engineering periodical collections of 23 engineering college/schools in relation to up-to-dateness, growth rate, strengths and weaknesses perceived by faculty members and engineering students.
The study covers the periodical collections of 23 engineering college/schools namely: Adamson University, Air Link International Aviation School, Alejandro Colleges, AMA-Makati, AMA-Quezon City, Central Colleges of the Philippines, De La Salle University, Don Bosco Technical School, FEATI University, Manuel L. Quezon University, NAMEI Polytechnic Institute, New Era University, Pamantasan ng Lungsod ng Maynila, PATTS, Philippines School of SCA, Polytechnic University of the Philippines, Rizal Technological University, St. Francis of Assissi Colleges, Technological University of the Philippines, University of Perpetual Help Rizal, University of Santo Tomas, University of the East and University of the Philippines. They were chosen by means of purposive convenience random sampling. These respondents assessed/evaluated the adequacy of the engineering library periodical collections utilizing a combination of impressionistic, checklist and quantitative methods.
The evaluation of the periodical collections of the 23 engineering schools revealed that the periodical collections of the University of the Philippines, De La Salle University, Central Colleges of the Philippines and University of Santo Tomas are outstanding. The faculty and students evaluated their periodical collections on engineering as very up-to-date. Furthermore, these were rated outstanding insofar as meeting the four levels of information needs of faculty and students, such as basic information, current and important information needs, basic materials for independent study and exhaustive research. The collections of the rest of the schools were rated barely sufficient. The rate of growth of engineering periodical titles of 23 engineering libraries was very small.
Four recommendations were given: (1) the TPEAME should come up with a standard checklist of engineering periodical titles in engineering; (2) libraries and faculty must come together to strengthen their periodical collection; (3) establish cooperative acquisitions; and (4) start the networking of these libraries.
Computer print out.
Vita.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Engineering periodicals -- Philippines -- Manila Metropolitan Area; Engineering periodicals -- Evaluation. -- Philippines -- Manila Metropolitan Area